A Simplified Model of the Kirchhoff Plate Resting on the Elastic Subsoil - Erdini, M.; Pauk, V.; Woźniak, M. (Engineering Transactions, 1997)
An approximate 2D-model is proposed for the analysis of thin plates resting on a two-parameter subsoil layer. The model obtained is discretized and applied to calculations of uniformly loaded square plates. The scope of applicability of the analytical formulae for the plate deflections and curvatures is evaluated.